Fluctuation of fasting blood glucose in patients who underwent primary or revision total joint arthroplasty: a retrospective review - Ye, Yongyu; Pan, Baiqi; Gu, Minghui; Xian, Guoyan; Chen, Weishen; Zheng, Linli; Zhang, Ziji; Sheng, Puyi (Journal of orthopaedic surgery and research, 2020)
Background Perioperative hyperglycemia is a risk factor for postoperative complications after total joint arthroplasty (TJA). However, the variability of fasting blood glucose (FBG) after TJA remains unknown. We aimed to assess the fluctuation and extent of elevation of FBG following primary or revision TJA. Methods We retrospectively evaluated the medical records of 1788 patients who underwent primary or revision TJA between 2013 and 2018. We examined FBG values collected during 6 days of the perioperative period. The findings for each time point were evaluated with descriptive statistics. Postoperative glycemic variability was assessed by the coefficient of variation (CV). Results The final cohort included the medical records of 1480 patients (1417 primary and 63 revision). FBG was highest on postoperative day 1 in the primary and revision groups (P < 0.001), which had the highest number of hyperglycemic patients (FBG > 100 mg/dL), with 66.4% and 75.5% in the primary and revision groups, respectively. The CV of diabetics in the primary group, and diabetics and non-diabetics in the revision group, was higher than that of non-diabetics in the primary group. Conclusion Postoperative day 1 showed the highest FBG levels and proportion of patients with hyperglycemia in the perioperative period. Primary group diabetics, and revision group diabetics and non-diabetics, had higher postoperative fluctuation of FBG than primary group non-diabetics. Frequent FBG monitoring may therefore be warranted in diabetic patients undergoing TJA, and all patients undergoing revision TJA.